Innovative Work Behavior: An association of Leadership Styles, Job Autonomy, and Employee Proactive Behavior (Journal of Social Sciences Review, 2023)
The goal of this study is to examine the function of job autonomy, proactive employee behaviour, and prestige & dominance leadership styles as an interpreter of innovative work behaviour. The sample of this research was taken from 269 employees of public power generation plants and independent power producers of Pakistan using a purposive sampling technique. Using Smart-PLS 3.0 as a statistical tool, data was processed, and hypotheses were verified using structural equation modelling (SEM). The results of this study show that all hypotheses are supported, and that employee proactive behavior, job autonomy, and leadership styles that emphasise prestige and dominance all have a positive and significant impact on innovative work behaviour.  Findings provided practical understandings for employees in electricity power generation companies of Pakistan to consider prestige leadership style, dominance leadership style, job autonomy, and proactive employee behavior for increasing employee innovative work behavior. This could contribute to improve the innovation index of the country.
Keywords: Prestige Leadership Style; Dominance Leadership Style; Job Autonomy; mployee Proactive Behavior; Innovative Work Behavior